Analysis of Critical Thinking Ability of Phase E Students in Biology Learning at SMA Negeri 1 Koto Balingka: The - Eka Putri, Alya; Lufri, Lufri (Al-Alam: Islamic Natural Science Education Journal, 2025)
Critical thinking skills represent a core competency in 21st-century biology education, as they enable students to grasp concepts deeply and address problems logically. This study evaluates the level of critical thinking abilities among Phase E students at SMA Negeri 1 Koto Balingka. It employs a descriptive quantitative approach, utilizing a questionnaire developed from critical thinking indicators. Data analysis is conducted descriptively to illustrate achievements across each indicator. The findings reveal that students' critical thinking remains at a moderate to adequate level, particularly in constructing logical arguments and explaining concepts scientifically. This highlights the need for more innovative and effective teaching strategies to optimize the development of students' critical thinking skills.